The Problematics of Applying Living Law as a Basis for Criminalization in the Indonesian Criminal Code - Iwan Kurniawan; Riki Afrizal; Putra, Antoni (Jurist-Diction, 2026)
The application of the living law concept within Indonesia’s criminal law system, as regulated in the new Criminal Code (KUHP), opens a new dimension in recognizing customary law and social norms that exist within society. This concept seeks to create a legal system that is more responsive to social and cultural diversity, while accommodating local norms within the criminal justice process. However, the recognition of living law also raises significant issues, particularly with respect to the principle of legality in criminal law, legal uncertainty, and the potential for abuse of power by law enforcement authorities. This study aims to analyze the problems associated with the implementation of living law as a basis for criminalization under the KUHP, using a normative juridical approach and relying on both primary and secondary legal sources. The discussion includes the identification of challenges arising from the ambiguity in the acceptance and proof of customary norms in legal practice, as well as these norms’ impact on legal certainty and the protection of human rights. Furthermore, this article proposes alternative approaches to the application of living law that are more selective and firmly grounded in the principles of justice and human rights. The findings indicate that although living law can enhance respect for legal pluralism, its implementation must go through strict and transparent verification mechanisms to prevent legal uncertainty and discrimination. Therefore, clear regulations are needed regarding the recognition and limitations of living law norms within the criminal justice system, along with a more restorative approach to dispute resolution.